2022
DOI: 10.1007/s00404-022-06647-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transdermal versus oral hormone replacement therapy in postmenopause: a systematic review

Abstract: Purpose To summarize available evidence comparing the transdermal and the oral administration routes of hormone replacement therapy (HRT) in postmenopausal women. Methods We performed a systematic review of the literature on multiple databases between January 1990 and December 2021. We included randomized controlled trials and observational studies comparing the transdermal and oral administration routes of estrogens for HRT in postmenopausal women regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 89 publications
(94 reference statements)
0
11
0
1
Order By: Relevance
“…Eleven randomized trials have compared lipid effects of oral versus transdermal HT. 41 These trials have consistently found that, in contrast with oral HT, which increases triglycerides by 5% to 15%, transdermal HT decreases triglyceride levels by 5% to 30% 41,60,61 (Table 5). In this context, we recommend the transdermal route of ET for symptomatic menopausal women with dyslipidemia, particularly those with a tendency toward hypertriglyceridemia.…”
Section: Recommendations For Htmentioning
confidence: 97%
See 2 more Smart Citations
“…Eleven randomized trials have compared lipid effects of oral versus transdermal HT. 41 These trials have consistently found that, in contrast with oral HT, which increases triglycerides by 5% to 15%, transdermal HT decreases triglyceride levels by 5% to 30% 41,60,61 (Table 5). In this context, we recommend the transdermal route of ET for symptomatic menopausal women with dyslipidemia, particularly those with a tendency toward hypertriglyceridemia.…”
Section: Recommendations For Htmentioning
confidence: 97%
“…No randomized controlled trials have compared VTE risk with oral versus transdermal versus placebo therapy. However, observational studies have consistently observed lower rates of VTE with transdermal compared with oral HT 39–41 (Table 3). Moreover, in 11 randomized controlled studies of lipid metabolism, transdermal HT has shown neutral effects on triglycerides, in contrast with oral HT, which increases triglyceride levels.…”
Section: Types Of Htmentioning
confidence: 98%
See 1 more Smart Citation
“…The determination of whether vasomotor symptoms are moderate to severe is based on each patient’s assessment of their symptoms and whether they are bothersome, interfere with daily activities, or both. Because of the potential adverse effects of hormone therapy (eg, increased risk of venous thromboembolism, stroke, and breast cancer with combined estrogen plus progestogen therapy) (Table 2 and eTables 17-23 in the Supplement), vasomotor symptoms should only be treated if they are bothersome. Clinicians should prescribe the lowest effective dose of hormone therapy for the shortest duration consistent with the patient’s needs, with periodic reevaluation of the need for continued hormone therapy to control symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In the wake of the Women's Health Initiative study, the use of ET initially decreased and then began to transition from oral to transdermal formulations, presumably because of a hypothesized lower risk of adverse outcomes 3-6 . However, the risk difference between formulations has yet to be fully elucidated 7-10 . Much of the risk (and benefit) associated with the use of ET is thought to be related to the amount and duration of estrogen exposure 11,12 .…”
mentioning
confidence: 99%